How the Brunswikian Lens Model Illustrates the Relationship Between Physiological and Behavioral Signals and Psychological Emotional and Cognitive States - Burgoon, Judee K.; Wang, Rebecca Xinran; Chen, Xunyu; Ge, Tina Saiying; Dorn, Bradley (Frontiers in Psychology, 2022)
Social relationships are constructed by and through the relational communication that people exchange. Relational messages are implicit nonverbal and verbal messages that signal how people regard one another and define their interpersonal relationships—equal or unequal, affectionate or hostile, inclusive or exclusive, similar or dissimilar, and so forth. We report an investigation that explored how interactants in groups signal these messages through perceptual data and behaviors measured by sensor data. Using a modified Brunswikian lens model, we explored which automatically measured kinesic, vocalic and linguistic indicators predicted perceived relational messages of dominance, affection, involvement, composure, similarity, and trust and those in turn predicted deception.